Liver stiffness regression after successful Hepatitis C treatment is independent of HIV coinfection1. Issue 3 (27th January 2019) - Malin, JJ; Boesecke, C; Schwarze‐Zander, C; Wasmuth, JC; Schlabe, S; Trebicka, J; Spengler, U; Llibre, JM; Jou, T; Vasylyev, M; Clotet, B; Rockstroh, JK
Abstract : Objectives: The aim of the study was to assess the regression of liver stiffness after successful direct‐acting antiviral (DAA) treatment in patients with hepatitis C virus (HCV) monoinfection and HCV/‐HIV coinfection. In addition, we aimed to identify factors associated with liver stiffness regression. Methods: We studied patients treated with interferon‐free DAA regimens with a sustained virological response at week 12 (SVR12 ) or 24 (SVR24 ) post‐treatment. Liver stiffness was assessed by transient elastography (TE) before the initiation and after the end of treatment (median 12 weeks). Results: Of 214 enrolled patients, 85 (40%) were HCV monoinfected and 129 (60%) HCV/HIV coinfected. Baseline median TE values were 7.8 kPa [interquartile range (IQR) 5.9–12.0 kPa] in mono‐infected patients and 10.7 kPa (IQR 7.8–17.0 kPa) in coinfected patients. Overall, the median TE value decreased from 10.1 to 6.8 kPa ( n = 214; P < 0.0001). There was no difference between mono‐ and coinfected patients (−2.2 versus −3.3 kPa, respectively; P = 0.88), which was verified by an analysis of covariance (ANCOVA) adjusting for baseline TE values. Significant (≥ 30%) regression of liver stiffness was achieved by 45% of patients (54% with baseline TE ≥ 7.1 kPa). In multivariate analysis, a prior HCV treatment was a negative predictor of liver stiffness regression [odds ratio (OR) 0.31; P = 0.001]. A higher baseline TE value was positively associated with achieving a significant regression (OR 1.06; P = 0.02). HIV coinfection status, HCV genotype, age, sex, treatment duration, controlled attenuation parameter value, bilirubin concentration, platelet count and aspartate aminotransferase concentration were not associated with liver stiffness regression. Conclusions: Regression of liver stiffness after successful DAA treatment did not differ in patients with HCV monoinfection and those with HCV/HIV coinfection. Half of all patients achieved a significant (≥ 30%) regression. Prior treatment for HCV was a negative predictor for this endpoint, while a higher baseline TE value was positively associated with regression.